The Role of Artificial Intelligence in Personalized and Adaptive Learning Environments - Farhan Idris Jameel; Rayyan Saif Imran (Proceeding of the International Conference on Global Education and Learning, 2024)
The integration of Artificial Intelligence (AI) in personalized and adaptive learning environments has revolutionized the education sector by offering customized learning experiences tailored to individual student needs. This study explores the role of AI in enhancing adaptive learning through data-driven insights, intelligent tutoring systems, and real-time feedback mechanisms. By employing machine learning algorithms and natural language processing, AI-driven platforms can analyze student performance, predict learning patterns, and deliver personalized content. The study highlights the effectiveness of AI in addressing diverse learning styles, improving engagement, and optimizing educational outcomes. Furthermore, it discusses the implications of AI in fostering inclusive education and lifelong learning. The findings suggest that AI-powered learning environments significantly enhance student-centered education, promoting efficiency and accessibility.